2018
DOI: 10.1038/s41598-018-33214-3
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Thymoquinone on radiation enteritis in mice

Abstract: Radiation enteritis is an old but emerging question induced by the application of radiation. However, no effective drugs for radiation enteritis in clinic. In this study, we found that thymoquinone (TQ) could mitigate intestinal damages induced by irradiation. After exposure to irradiation, TQ-treated improved the irradiated mice survival rate, ameliorated intestinal injury and increased the numbers of intestinal crypts. Furthermore, Lgr5+ ISCs and their daughter cells, including Vil1+ enterocytes, Ki67+ cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…TQ is also reported in other plants such as Nepeta Leucophylla, Tetraclinis articulata, Juniperus Cedrus, Callitris quadrivalvis, Monarda fistulosa etc. It has also been reported in genus Tetraclinis, Cupressus, and Juniperus of the Cupressaceae family (Hou et al, 2018).…”
Section: Source and Occurrence Of Thymoquinonementioning
confidence: 74%
See 1 more Smart Citation
“…TQ is also reported in other plants such as Nepeta Leucophylla, Tetraclinis articulata, Juniperus Cedrus, Callitris quadrivalvis, Monarda fistulosa etc. It has also been reported in genus Tetraclinis, Cupressus, and Juniperus of the Cupressaceae family (Hou et al, 2018).…”
Section: Source and Occurrence Of Thymoquinonementioning
confidence: 74%
“…Besides Ranunculaceae, where only minute quantities of TQ are found, its presence has also been confirmed in other genera of Laminaceae family like Agastache, Coridothymus, Monarda, Mosla, Origanum, Satureja, Thymbra, and Thymus (Hou et al, 2018) . In plants, TQ is found along with its dimeric and reduced forms dithymoquinone and thymohydroquinone, the latter being a compound with significant biological activities (Imran et al, 2018).…”
Section: Source and Occurrence Of Thymoquinonementioning
confidence: 83%
“…Interestingly, there is a positive correlation between the number of Paneth cells and the number of Lgr5 + stem cells [ 39 ]. The hyperplastic cells of the small intestinal epithelium can be identified due to the expression of the proliferation marker protein Ki67 [ 40 ]. We found that HL-003 significantly prevented the irradiation-induced decrease in Lgr5 + ISCs, Ki67 + TACs, and lysozyme + Paneth cells, and it promoted the regeneration, differentiation, and proliferation of intestinal epithelial cells and maintained homeostasis of the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, IR can impair the structure of DNA, proteins and lipids, and eventually lead to deleterious consequences, including cell apoptosis and organ system dysfunction 6‐8 . Research has shown that hematopoietic tissues and the gastrointestinal (GI) tract are sensitive to IR, the former being the most sensitive, 9,10 and there are few effective methods to prevent or mitigate radiation‐induced injury of the GI tract 11,12 . Thus, finding remedies to protect these systems from radiation damage is of utmost importance 13,14 …”
Section: Introductionmentioning
confidence: 99%